Challenges faced by Small Medium Enterprises (SMEs) exporters’ in Malaysia / Khaulah Mohammad Zaki - Mohammad Zaki, Khaulah (Faculty of Business and Management, 2018)
This research and study was conducted to know the challenges faced by the SMEs in exporting at Malaysia. It is also indicating the relationship between the dependent variable (challenges in exporting) and independent variable (distribution access, human capital and export market attractiveness). This research is quantitative research and the data used for the study was collected using distribution of questionnaires. There were 70 respondents took part in answering the questionnaires. The data obtained from the questionnaires were analyzed by using SPSS software. As a summary, after analyzing the data collected, the result showed that only one has significance relationship with the dependent variable, which are human capital.